Metal‐Organic Framework Beads: Porous Metal–Organic Framework@Polymer Beads for Iodine Capture and Recovery Using a Gas‐Sparged Column (Adv. Funct. Mater. 30/2018). (23rd July 2018) - Valizadeh, Bardiya; Nguyen, Tu N.; Smit, Berend; Stylianou, Kyriakos C.
Abstract : In article number1801596, Kyriakos C. Stylianou and co‐workers devise a polymeric body with a crystalline heart. Phase inversion is used to shape metal–organic framework (MOF) powders into millimeter‐sized MOF‐polymer spherical beads. The composite beads outperform MOF powders toward the capture and recovery of iodine.